2020
DOI: 10.21203/rs.3.rs-83583/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and Characterization of an Efficient Mutant Resource of the Mega Variety, Samba Mahsuri for Rice Improvement

Abstract: Background:Novel variants of rice (Oryza sativa L.) can be obtained from induced mutations. The objective of the present study is to induce mutations in the background of Samba Mahsuri (BPT-5204), a popular and mega rice variety of India for creating novel variants for morphological, physiological and biotic stresses through using Ethyl Methane Sulphonate (EMS).Results: A population derived from 10, 500 M1 plants and their descendants was phenotyped for a wide range of traits leading to the identification of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Further, Oladasu et al [10] performed a cluster analysis on rice mutants and parents using ISSR markers and reported that the genetic similarity coefficient ranged from 0.17 to 0.63, which is in agreement with the genetic Gower distance (0.04-0.38) obtained in the present study. Furthermore, Kumar and Bhagwat [56], Oladasu et al [10], Truong et al [44], Suneel et al [54], Potupureddi et al [53] and Andrew-Peter et al [55] also performed UPGMA-based cluster analyses on rice mutants and parents and reported similar findings as reported in the current study. Furthermore, the principal component analysis (PCA)-based scatter plot prepared over the principal coordinate 1 (PC1) and principal coordinate 2 (PC2) clearly demonstrated the patterns of the three major groups' (A, B and C) differentiations (Figure 10).…”
Section: Ssr Marker-based Genetic Diversity Study In Rice Genotypessupporting
confidence: 84%
See 1 more Smart Citation
“…Further, Oladasu et al [10] performed a cluster analysis on rice mutants and parents using ISSR markers and reported that the genetic similarity coefficient ranged from 0.17 to 0.63, which is in agreement with the genetic Gower distance (0.04-0.38) obtained in the present study. Furthermore, Kumar and Bhagwat [56], Oladasu et al [10], Truong et al [44], Suneel et al [54], Potupureddi et al [53] and Andrew-Peter et al [55] also performed UPGMA-based cluster analyses on rice mutants and parents and reported similar findings as reported in the current study. Furthermore, the principal component analysis (PCA)-based scatter plot prepared over the principal coordinate 1 (PC1) and principal coordinate 2 (PC2) clearly demonstrated the patterns of the three major groups' (A, B and C) differentiations (Figure 10).…”
Section: Ssr Marker-based Genetic Diversity Study In Rice Genotypessupporting
confidence: 84%
“…Similarly, Potupureddi et al [53] and Suneel et al [54] also obtained 85.0-98.3% genomic similarity between the rice mutants and parents using SSR markers. Moreover, Andrew-Peter et al [55] also reported the minimum dissimilarity and maximum similarity values between mutants and parents in rice.…”
Section: Ssr Marker-based Genome Similarity Study In Rice Mutants And...mentioning
confidence: 78%